Monodisperse biodegradable transarterial radioembolism polymer microsphere capable of loading yttrium-90 and preparation method of monodisperse biodegradable transarterial radioembolism polymer microsphere
By performing specific functional treatment on the surface of chitosan microspheres, biodegradable yttrium-90 microspheres were prepared, which solved the problems of high density, fast settlement and unstable adsorption in the existing microspheres, achieving uniform distribution of microspheres in the blood and the stability of multiple doses, and improving the effect of liver cancer treatment.
Patent Information
- Application Number
- CN202411983444.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-04
AI Technical Summary
The existing yttrium-90 microspheres have high density, fast settlement, unstable adsorption, and non-biodegradable, resulting in difficulty in uniform distribution in the blood and difficulty in repeated doses of multiple doses, affecting the therapeutic effect.
By grafting polyglycidyl methacrylate on the surface of chitosan microspheres with controllable particle size and performing iminodiacetic acid functionalization, monodispersible, biodegradable, and controllable particle size polymer material microspheres were prepared to achieve stable load on yttrium-90.
The prepared microspheres have good dispersibility and sedimentation properties, and the yttrium-90 load is stable. The microspheres can be biodegradable under physiological conditions and are suitable for multiple doses, which improves the therapeutic effect.
Smart Images

Figure CN119746136A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of embolic microsphere preparation, and in particular to a method for preparing a monodisperse, biodegradable, and size-controllable polymer material microsphere capable of loading yttrium-90. Technical Background
[0002] Hepatocellular carcinoma (HCC) is one of the most common causes of cancer death worldwide, with extremely high mortality and recurrence rates. The World Health Organization estimates that by 2020, 905,700 people will be diagnosed with liver cancer and 830,200 people will die from it, with more than 70% of patients having already reached a stage where surgical resection or liver transplantation is not possible. Therefore, the treatment of liver cancer has become an important issue concerning all of humanity.
[0003] As an important organ of the human body, 70% of the blood supply of the liver comes from the portal vein, and more than 80% of the nutrients necessary for liver cancer cells are delivered through the hepatic artery. This characteristic of liver tumors makes it possible to use different treatment methods. At present, the clinical treatment methods for HCC include surgical resection, liver transplantation, local percutaneous ablation, transarterial chemoembolization (TACE), transarterial radioembolization (TARE), etc. For these methods, liver transplantation treatment is subject to many restrictions due to the high price, scarcity of liver sources and the influence of human rejection. Surgical treatment and ablation treatment are mostly suitable for early liver cancer. For most patients with advanced liver cancer who have lost the opportunity for surgical and ablation treatment, interventional treatment (including TARE and TACE) seems to be the only palliative treatment method. Compared with TACE, TARE involves the targeted delivery of radioactive isotope yttrium-90 labeled microspheres to the tumor supply artery through an arterial catheter, thereby providing controlled radiation exposure to the tumor and inducing its apoptosis to achieve the treatment purpose. Generally, TARE is more effective than TACE in terms of fewer side effects, high efficacy and short treatment time. Since 1998, TARE technology has been clinically applied in more than 50 countries and regions around the world, including Australia, the European Union, and Canada, with significant efficacy in treating advanced liver cancer. In recent years, my country has also begun the research and development of TARE clinical treatment and related microspheres.
[0004] Currently, commercial yttrium-90 microspheres mainly include yttrium-90 glass microspheres and yttrium-90 resin microspheres that are approved for marketing. However, the non-biodegradability and relatively high density of these commercial microspheres may hinder their uniform distribution in the blood, thereby increasing the difficulty of injection and greatly hindering their repeated dosing, significantly affecting the final therapeutic effect. Therefore, it is crucial to develop a monodisperse, biodegradable, appropriately dense, and stably adsorbed yttrium-90 TARE microsphere.
[0005] In recent years, some researchers have developed radioactive microspheres from biomass-derived materials such as chitosan, silk fibroin, and polylactic acid copolymers. Among them, chitosan, as one of the most abundant natural polysaccharide biopolymers, has attracted increasing attention in the fields of drug delivery, surgical treatment, antibacterial therapy, and vaccines due to its high biocompatibility, non-toxicity, easy availability, biodegradability, and easy modification. Obviously, these properties make it an ideal candidate material for the production of biodegradable TARE microspheres. So far, no research has reported the preparation of a monodisperse biodegradable chitosan-based TARE microsphere that can effectively label yttrium-90 for HCC treatment. Summary of the invention
[0006] The purpose of the present invention is to synthesize a monodisperse, biodegradable, size-controllable, yttrium-loaded 90 Y) Chitosan-based microspheres with stable performance to overcome the problems of existing yttrium-90 microspheres such as high density, fast sedimentation, unstable adsorption and non-degradability.
[0007] In order to achieve the above-mentioned invention object, the technical solution provided by the present invention is as follows:
[0008] Monodisperse biodegradable transarterial radioembolization polymer microspheres capable of loading yttrium-90 were prepared by grafting poly(glycidyl methacrylate) and functionalizing with iminodiacetic acid on the surface of chitosan microspheres with controllable particle size. The preparation steps are as follows:
[0009] S1. Preparation of chitosan microspheres with controllable particle size by direct membrane emulsification method;
[0010] S2, grafting poly(glycidyl methacrylate) on the surface of chitosan microspheres to obtain poly(glycidyl methacrylate) grafted chitosan microspheres;
[0011] S3. Functionalizing the surface of poly(glycidyl methacrylate) grafted chitosan microspheres with iminodiacetic acid to obtain monodisperse biodegradable trans-arterial radioembolization polymer microspheres capable of loading yttrium-90.
[0012] Furthermore, the preparation of chitosan microspheres with controllable particle size comprises the following steps:
[0013] S11, adding a surfactant and petroleum ether dropwise to liquid paraffin, and stirring thoroughly to obtain solution A;
[0014] S12, weigh chitosan powder and dissolve it in acetic acid solution, stir it with ultrasound until the solution is clear, and then let it stand for 12 hours to obtain solution B;
[0015] S13, pouring the solution A in step into a direct membrane emulsification device, under inert gas pressure, solution A passes through a hydrophobic microporous ceramic membrane and then enters solution B, and a uniform water-in-oil (W / O) emulsion is obtained under magnetic stirring at 300 rpm; adding crosslinking agent glutaraldehyde to the obtained emulsion, and solidifying it under magnetic stirring at 40°C; collecting the product by centrifugation, washing it with petroleum ether, anhydrous ethanol and water for 3 times respectively, and then freeze-drying it for 24 hours to obtain chitosan microspheres with an average particle size of 20 μm.
[0016] Preferably, in step S11, the surfactant is any one of W / O emulsifiers span80 and span85; the volume ratio of liquid paraffin: petroleum ether: surfactant is 200:50:10.
[0017] Preferably, the chitosan described in step S12 has a deacetylation degree of 95% and a molecular weight of 1×10 5 Da; the concentration of the acetic acid solution is 3wt%; the mass ratio of the chitosan powder to the acetic acid solution is 1:80.
[0018] Preferably, in step S13, the average pore size of the hydrophobic microporous ceramic membrane tube is 19.9 μm; the volume ratio of solution A, solution B and cross-linking agent is 25:260:2; the gas pressure is 1.5±0.5 kPa; the magnetic stirring reaction time is 4 h; and the centrifugal speed is 10000 rpm.
[0019] Preferably, the synthesis route for preparing chitosan microspheres with controllable particle size in step S1 is as follows:
[0020]
[0021] Furthermore, grafting poly(glycidyl methacrylate) on the surface of chitosan microspheres comprises the following steps:
[0022] S21, dispersing the chitosan microspheres described in S1 into water, stirring with ultrasound until a stable suspension is formed, then transferring to a three-necked flask, stirring and heating to 60° C. under nitrogen protection;
[0023] S22, adding initiator FeSO4·7H2O and potassium persulfate to the mixture in sequence, reacting for 1 hour, and then adding glycidyl methacrylate to react for 12 hours;
[0024] S23, washing the microspheres: washing with anhydrous ethanol and water for three times, centrifuging at 10000 rpm for 2 min, and freeze-drying to obtain poly(glycidyl methacrylate) grafted chitosan microspheres.
[0025] Preferably, the mass ratio of chitosan microspheres, glycidyl methacrylate and water in step S21 is 1:20:100.
[0026] Preferably, in step S22, the mass ratio of the initiator FeSO4·7H2O to potassium persulfate is 3:10.
[0027] Furthermore, functionalizing the surface of poly(glycidyl methacrylate) grafted chitosan microspheres with iminodiacetic acid comprises the following steps:
[0028] S31, dispersing the poly(glycidyl methacrylate) grafted chitosan microspheres described in S2 into water to form a stable suspension, and then adding iminodiacetic acid and sodium hydroxide;
[0029] S32, adjust the pH of the mixture to 10-11 with 2 mol / l Na2CO3, transfer to a three-necked flask, and heat to 80°C under nitrogen protection with stirring for 24 h;
[0030] S33. The product was washed with anhydrous ethanol and water respectively, and then freeze-dried to obtain chitosan microspheres (CPIs) that can stably load yttrium-90.
[0031] Preferably, in step S31, the mass ratio of iminodiacetic acid to sodium hydroxide is 3.32:2.10.
[0032] Preferably, the mass ratio of poly(glycidyl methacrylate) grafted chitosan microspheres to water is 1:100.
[0033] Preferably, the synthesis route for preparing chitosan microspheres capable of stably loading yttrium-90 in steps S2 and S3 is as follows:
[0034]
[0035] Scanning electron microscope observation shows that the polymer microspheres prepared by the present invention have a complete spherical structure, are uniform in size, and have a main particle size range of about 20.9±10 μm; the microspheres have a good dispersion effect in physiological saline and excellent sedimentation performance within 5 minutes.
[0036] After the microspheres prepared by the method of the present invention are loaded with yttrium, there is no leakage of yttrium in phosphate buffered saline (PBS) within 24 hours, and the microspheres show obvious biodegradation in the sixth week under the condition of culturing in fetal bovine serum at 37°C. The monodisperse biodegradable transarterial radioembolization polymer microspheres loaded with yttrium-90 prepared by the above method are used in the preparation of liver cancer radiotherapy drugs.
[0037] Compared with the prior art, the present invention can achieve the following technical effects:
[0038] (1) The reagents used in the experimental process of the present invention are easy to clean and remove, and there is no complicated process of removing harmful impurities such as acid washing and alkali washing. The synthesized microspheres are polymer microspheres that can load yttrium-90. The base material is a natural cationic polysaccharide polymer - chitosan, which has the advantages of high biocompatibility, non-toxicity, easy modification, and easy availability. The microspheres have complete sphericity, a suitable particle size range, and considerable biodegradability. Compared with commercial resin microspheres that completely settle in physiological saline in 7 seconds, the microspheres prepared by the present invention have good dispersibility and sedimentation performance within 5 minutes, which is more convenient for clinical injection practice.
[0039] (2) After loading yttrium, nearly 99% of the yttrium was stably loaded on the surface of the microspheres in physiological saline for 24 hours. At the same time, the yttrium-loaded microspheres have more stable properties in PBS. The polymer microspheres prepared by the present invention have excellent adsorption stability for yttrium and have broad market prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 3 is a SEM image of monodisperse polymer microspheres capable of loading yttrium-90 in an embodiment of the present invention.
[0041] Figure 2 It is the particle size distribution result of the polymer microspheres in the example.
[0042] Figure 3 It is the dispersion and sedimentation performance state of the polymer microspheres in physiological saline and PBS in the embodiment.
[0043] Figure 4 This is the result of the natural biological degradation of the polymer microspheres in the embodiment.
[0044] Figure 5 This is the adsorption stability result after the polymer microspheres are loaded with yttrium in the example. DETAILED DESCRIPTION
[0045] Example 1
[0046] The preparation of chitosan microspheres with controllable particle size comprises the following steps:
[0047] Dissolve 1g chitosan powder in 80ml 3wt% acetic acid solution and ultrasonically stir until no clarification, then stand for 12h to obtain solution A. Mix 200ml liquid paraffin, 50ml petroleum ether, and 10ml span80 and stir for 30min to obtain solution B. Take 25ml solution A and add it to the direct membrane emulsification device. Under a nitrogen pressure of 1.5±0.5kpa, it enters solution B through a hydrophobic ceramic membrane tube with an average pore size of 19.9μm. Stir magnetically at 300rpm to obtain a uniform W / O emulsion, then add 2ml glutaraldehyde solution to the emulsion and react at 40℃ for 4h. The obtained product was washed 3 times with petroleum ether, anhydrous ethanol, and water, respectively, and freeze-dried for 24h to obtain chitosan microspheres with controllable particle size.
[0047] Example 2
[0048] The preparation of chitosan polymer microspheres capable of loading yttrium-90 comprises the following steps:
[0049] 0.5g chitosan microspheres were dispersed in 50ml water, and ultrasonically stirred until a stable suspension was formed, then transferred to a three-necked flask, heated and stirred to 60°C under a nitrogen atmosphere, 0.03g FeSO4·7H2O and 0.1g potassium persulfate were added in sequence, and 10ml glycidyl methacrylate was slowly added dropwise after 1h to react for 12h. The obtained product was washed with anhydrous ethanol and water for 3 times, and freeze-dried for 24h to obtain poly(glycidyl methacrylate) grafted chitosan microspheres. 0.5g poly(glycidyl methacrylate) grafted chitosan microspheres were dispersed in 50ml water to form a stable suspension, and 3.32g iminodiacetic acid and 2.10g sodium hydroxide were added, and the pH of the mixture was adjusted to 10-11 with 2mol / L Na2CO3 solution. The mixture was transferred to a three-necked flask, stirred and heated to 80°C under a nitrogen atmosphere for 24h. The obtained product was washed and dried to obtain chitosan polymer microspheres capable of loading yttrium-90. The microspheres had good sphericity, suitable particle size distribution, and good dispersibility and sedimentation performance within 5 minutes. The results are shown in the attached figure. Figure 1 , 2 , as shown in Figure 3.
[0050] Example 3
[0051] The in vitro degradation experiment of the modified chitosan polymer microspheres includes the following steps:
[0052] CPIs (15 mg) were dispersed in 2.0 ml of fetal bovine serum (FBS) and incubated at 37°C with gentle shaking at 120 rpm for specific time periods (2, 4, 6, 8 and 10 weeks). The separated microspheres were washed 5 times with deionized water and freeze-dried to obtain biodegradable microspheres. The serum-cultured microspheres showed obvious signs of degradation at week 6. At week 10, the boundaries of the well-dispersed microspheres became blurred and almost completely adhered together, indicating that the microspheres had good biodegradability. The results are shown in the attached figure. Figure 4 shown.
[0053] Example 4
[0054] The adsorption stability experiment of modified chitosan polymer microspheres on yttrium includes the following steps:
[0055] The chitosan polymer microspheres prepared in Example 2 were loaded with yttrium and their adsorption stability was evaluated. The pH was 6, the yttrium concentration was 1-3 mmol / L, the solid-liquid ratio was 4:1 (g / L), the adsorption time was 2h, the temperature was 25°C, and the microspheres were separated and washed with normal saline 5 times. The yttrium-loaded and dried microspheres were dispersed in normal saline (pH 7.35-7.45) and PBS (pH 7.2-7.4) respectively, with a solid-liquid ratio of 4:1 (g / L), a temperature of 25°C, and oscillated in a water bath for a specific time. The microspheres were separated from the suspension with a 0.45μm microporous membrane syringe and the yttrium concentration in the liquid was measured. No yttrium leakage was found in the PBS of the microspheres loaded with yttrium, indicating that they have excellent adsorption stability. The results are shown in the attached figure. Figure 5 shown.
[0056] The above description shows and describes several preferred embodiments of the invention, but the invention is not limited to the form disclosed herein, and is intended to cover all such substitutions, modifications and variations that fall within the broad scope of the invention. Therefore, any omissions, modifications, equivalent substitutions, improvements, etc. made by those skilled in the art that do not depart from the spirit and scope of the invention should be within the scope of protection of the claims attached to the invention.
Claims
1. A monodisperse biodegradable polymer microsphere for transarterial radioembolization loaded with yttrium-90, characterized in that: The chitosan microspheres are prepared by grafting poly(glycidyl methacrylate) and functionalizing with iminodiacetic acid on the surface of the chitosan microspheres with controllable particle size.
2. The method for preparing monodisperse biodegradable trans-arterial radioembolization polymer microspheres loaded with yttrium-90 according to claim 1, characterized in that: The following steps are involved: S1. Preparation of chitosan microspheres with controllable particle size by direct membrane emulsification method; S2, grafting poly(glycidyl methacrylate) on the surface of chitosan microspheres to obtain poly(glycidyl methacrylate) grafted chitosan microspheres; S3. Functionalizing the surface of poly(glycidyl methacrylate) grafted chitosan microspheres with iminodiacetic acid to obtain monodisperse biodegradable trans-arterial radioembolization polymer microspheres capable of loading yttrium-90.
3. The preparation method according to claim 2, characterized in that: The synthetic route for preparing chitosan microspheres with controlled particle size described in S1 is as follows: The preparation of chitosan microspheres with controllable particle size described in S1 comprises the following steps: S11, adding a surfactant and petroleum ether dropwise to liquid paraffin, and stirring thoroughly to obtain solution A; S12, weigh chitosan powder and dissolve it in acetic acid solution, stir it with ultrasound until the solution is clear, and then let it stand for 12 hours to obtain solution B; S13, pouring the solution A in step into a direct membrane emulsification device, under a certain inert gas pressure, solution A passes through a hydrophobic microporous ceramic membrane and enters solution B, and a uniform water-in-oil (W / O) emulsion is obtained under magnetic stirring at 300 rpm, and an appropriate amount of cross-linking agent glutaraldehyde is added to the obtained emulsion, and solidified by magnetic stirring at 40°C, and the product is collected by centrifugation, washed with petroleum ether, anhydrous ethanol and water for 3 times, and then freeze-dried for 24 hours to obtain chitosan microspheres with an average particle size of 20 μm.
4. The preparation method according to claim 3, characterized in that: The surfactant in step S11 is any one of W / O emulsifiers span80 and span85; the volume ratio of liquid paraffin: petroleum ether: surfactant is 200:50:10, the chitosan in step S12 has a deacetylation degree of 95% and a molecular weight of 1×10 5 Da; the concentration of the acetic acid solution is 3wt%; the mass ratio of the chitosan powder to the acetic acid solution is 1:
80.
5. The preparation method according to claim 3, characterized in that: S13 The volume ratio of solution A, solution B and cross-linking agent glutaraldehyde is 25:260:2; the average pore size of the hydrophobic microporous ceramic membrane tube is 19.9μm; the gas pressure is 1.5±0.5kpa; the magnetic stirring time is 4h; the centrifugal speed of the centrifugal collection product is 10000rpm.
6. The preparation method according to claim 2, characterized in that: S2 grafting poly(glycidyl methacrylate) on the surface of chitosan microspheres comprises the following steps: S21, dispersing chitosan microspheres into water, stirring ultrasonically to form a suspension, and then transferring to a three-necked flask, stirring and heating to 60° C. under a nitrogen atmosphere; S22, adding initiator FeSO4·7H2O and potassium persulfate to the mixture in turn, reacting for 1 hour, and then adding glycidyl methacrylate to react for 12 hours; S23, washing the microspheres: washing with anhydrous ethanol and water for three times respectively, centrifuging at 10000 rpm for 2 min, and freeze-drying to obtain poly(glycidyl methacrylate) grafted chitosan microspheres.
7. The preparation method according to claim 6, characterized in that: The mass ratio of the chitosan microspheres, glycidyl methacrylate and water described in S21 and S22 is 1:20:100; the mass ratio of the initiator FeSO4·7H2O to potassium persulfate is 3:
10.
8. The preparation method according to claim 2, characterized in that: In the steps S2 and S3, the synthetic route for grafting and modifying the surface of chitosan microspheres is as follows: S3 described the functionalization of iminodiacetic acid on the surface of poly(glycidyl methacrylate) grafted chitosan microspheres The following steps are involved: S31, dispersing poly(glycidyl methacrylate) grafted chitosan microspheres into water to form a stable suspension, and then adding iminodiacetic acid and sodium hydroxide; S32, adjust the pH of the mixture to 10-11 with 2 mol / l Na2CO3, transfer to a three-necked flask, and heat to 80°C under nitrogen protection with stirring for 24 h; S33. The product was washed with anhydrous ethanol and water respectively, and then freeze-dried to obtain chitosan microspheres (CPIs) that can stably load yttrium-90.
9. The preparation method according to claim 8, characterized in that: The mass ratio of the iminodiacetic acid to the sodium hydroxide in S31 is 3.32:2.10; the mass ratio of the poly(glycidyl methacrylate) grafted chitosan microspheres to water is 1:
100.
10. Use of the monodisperse biodegradable trans-arterial radioembolization polymer microspheres loaded with yttrium-90 according to claim 1 in the preparation of liver cancer radiotherapy drugs.